THE INFLUENCE OF DIGITAL LITERACY ON THE UTILIZATION OF THE POPULATION ADMINISTRATION AND CIVIL REGISTRATION ONLINE SERVICE INFORMATION SYSTEM (SILAKAS) APPLICATION IN TANAH LAUT REGENCY - Ratih Putri Kusuma; Etin Indrayani (Jurnal Ilmu Pemerintahan Widya Praja, 2023)
The Population Administration and Civil Registration Online Service Information System (SILAKAS) is a digital technology-based application developed by the Tanah Laut Regency Government to streamline document management and population administration processes. However, the impact of digital literacy on SILAKAS utilization is understudied. This study fills the research gap by examining the influence of digital literacy on the utilization of SILAKAS for Population Administration and Civil Registration Online Services in Tanah Laut Regency. Employing a descriptive quantitative method, simple linear regression analysis is used to measure the impact of digital literacy on SILAKAS utilization. Data collection involved distributing 100 questionnaires to SILAKAS users through random sampling. The findings indicate a significant favorable influence of digital literacy on SILAKAS utilization in Tanah Laut District. The regression analysis yielded a coefficient of 0.608 (p < 0.001) and a coefficient of determination (R Square) of 0.416, suggesting that digital literacy accounts for 41.6 percent of the variation in SILAKAS utilization. This study concludes that digital literacy is crucial in enhancing the utilization of SILAKAS for Population Administration and Civil Registration Online Services in the Tanah Laut Regency. The findings highlight the importance of promoting digital literacy initiatives to empower users and maximize the benefits of digital solutions in administrative processes. Policymakers and practitioners can utilize the insights from this study to develop strategies for improving digital literacy and optimizing the utilization of online administrative services. Key words: Population Administration; Civil Registration; Online Service Information System (SILAKAS); Digital Literacy.